Antioxidant and emulsifying properties of a galactose-rich heteropolysaccharide from Plinia cauliflora peels - Miranda, Bruna M (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
In this study functional properties of a galactose-rich heteropolysaccharide (GH) were accessed. The bands of a galactose-rich polysaccharide were found in FTIR spectra, including those from the fingerprint region. GH was characterized as a dark-red material (L* 25.86 ± 0.75, a* 9.46 ± 1.01, b* 0.65 ± 0.14, Chroma 9.48 ± 1.02) with antioxidant activity of 21.5 ± 0.08, 12.1 ± 0.06 and 0.46 ± 0.04 mmol Trolox Eq/mg GH in FRAP, DPPH and ABTS, respectively. GH presented 44.9% of esterification degree and 10.73 ± 0. 01 mg of GAE/g. The production parameters of GH emulsions (GH concentration, time and ultrasound power) were optimized using a 23 Central Composite Rotatable Design (CCRD). Emulsion droplets presented particle size (d µm) varying from 0.823 ± 0.065 to 1.926 ± 0.151, polydispersity index (PDI) from 0.10 ± 0.05 to 0.40 ± 0.01 and zeta potential from -29.25 ± 3.98 to -33.75 ± 1.77. Finally, the high emulsifying activity (EA) (96.67%) and emulsion stability (ES) (97.44%) allow suggesting that GH is a promising polysaccharide for food applications